2018
DOI: 10.1007/s11250-018-1517-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of adenovirus and DNA vaccines co-expressing P39 and lumazine synthase proteins of Brucella abortus in BALB/c mice

Abstract: Brucella poses a great threat to animal and human health. Vaccination is the most promising strategy in the effort to control Brucella abortus (B. abortus) infection, but the currently used live vaccines interfere with diagnostic tests and could potentially result in disease outbreak. Therefore, new subunit vaccines and combined immunization strategies are currently under investigation. In this study, immunogenicity and protection ability of a recombinant adenovirus and plasmid DNA vaccine co-expressing P39 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…An adenovirus vector-based vaccine was developed for protection against brucellosis and expressed the p39 and BLS proteins of B. abortus . This vaccine successfully induced strong humoral and cellular immune responses in a mouse model ( 198 ).…”
Section: Immunitymentioning
confidence: 99%
“…An adenovirus vector-based vaccine was developed for protection against brucellosis and expressed the p39 and BLS proteins of B. abortus . This vaccine successfully induced strong humoral and cellular immune responses in a mouse model ( 198 ).…”
Section: Immunitymentioning
confidence: 99%
“…Antigen-delivery systems, such as attenuated viruses or bacteria, are essential for presenting B. abortus immunogenic antigens to the immune system cells. Recently, Lin et al designed an adenoviral vector expressing both p39 and lumazine synthase proteins of B. abortus , which elicited significant humoral and cellular immune responses, although pre-existing immunity against adenovirus could prevent a vaccine from working ( 165 ). There are several studies using liposomes as Brucella antigen-delivery systems.…”
Section: Other Vaccinesmentioning
confidence: 99%
“…Recently, Lin et al., (2018) designed an adenovirus vector based vaccine expressing both p39 and lumazin synthase proteins of B. abortus and applied this combined immunization strategy for Brucella vaccine development. A mouse model study indicated that this vaccine elicited significant humoral and cellular immune responses [111]. It is clear that overexpression of Brucella immunodominant antigens can promote protection efficacy against brucellosis.…”
Section: Main Textmentioning
confidence: 99%